The Effects of Bilirubin and Lumirubin on the Differentiation of Human Pluripotent Cell-Derived Neural Stem Cells - Nikola Capková; Veronika Pospíšilová; Veronika Fedorová; Jan Raška; Kateřina Pospíšilová; Matteo Dal Ben; Aleš Dvořák; Jitka Viktorová; Dáša Bohačiaková; Libor Vítek (MDPI AG, 2021)
The 'gold standard' treatment of severe neonatal jaundice is phototherapy with blue-green light, which produces more polar photo-oxidation products that are easily excreted via the bile or urine. The aim of this study was to compare the effects of bilirubin (BR) and its major photo-oxidation product lumirubin (LR) on the proliferation, differentiation, morphology, and specific gene and protein expressions of self-renewing human pluripotent stem cell-derived neural stem cells (NSC). Neither BR nor LR in biologically relevant concentrations (12.5 and 25 µmol/L) affected cell proliferation or the cell cycle phases of NSC. Although none of these pigments affected terminal differentiation to neurons and astrocytes, when compared to LR, BR exerted a dose-dependent cytotoxicity on self-renewing NSC. In contrast, LR had a substantial effect on the morphology of the NSC, inducing them to form highly polar rosette-like structures associated with the redistribution of specific cellular proteins (β-catenin/N-cadherin) responsible for membrane polarity. This observation was accompanied by lower expressions of NSC-specific proteins (such as SOX1, NR2F2, or PAX6) together with the upregulation of phospho-ERK. Collectively, the data indicated that both BR and LR affect early human neurodevelopment in vitro, which may have clinical relevance in phototherapy-treated hyperbilirubinemic neonates.